GLS detrending for nonlinear unit root tests - George Kapetanios; Yongcheol Shin (Queen Mary University of London, Department of Economics, 2002)
This paper investigates GLS detrending procedures for unit root tests against nonlinear stationary alternative hypotheses where deterministic components are assumed present in the series under investigation. It is found that the proposed procedures have considerable power gains in a majority of cases against both existing nonlinear unit root tests and standard unit root tests.
Keywords: C12; C22; F31; 330; Detrending; Nonlinear unit root tests; Nonlinearity; STAR models; SETAR models; Unit Root Test; Methode der kleinsten Quadrate; Nichtlineares Verfahren